Socio-economic benefit and profitability analyses of Austrian hydro storage power plants supporting increasing renewable electricity generation in Central Europe. (June 2019) - Dallinger, Bettina; Schwabeneder, Daniel; Lettner, Georg; Auer, Hans
Abstract: Increasing flexibility in electricity systems with high-shares of volatile renewable generation is on top of the European policy making agenda. Large-scale pumped hydro storages are appropriate technology candidates to accomplish this. Therefore, they are one of the focus technologies of the European Commission in the Projects of Common Interest discussion. In order to get listed a thorough system benefit analysis has to be conducted. This paper investigates a comprehensive socio-economic benefit analysis of storage technologies according to the indicators expected by the European Commission. The dispatch model EDisOn + Balancing is applied, which includes the functionalities depicting balancing mechanisms. Additionally, the profitability analysis tries to sort out the most convincing business cases where storage technologies contributing to more flexibility in the electricity system can sustain in the long-run. A simulation tool has been developed to model and quantify flexibility options, and to evaluate the profitability from the owner's point-of-view. The results show that in Central Europe with increasing storage capacities the necessity of reserve capacity and investments in peaking units decreases while maintaining a high security of supply level. In addition to electricity generation and balancing cost reductions, shedding of renewables and significant amounts of environmental damage costs of up to 1300 MEuro/a can be avoided. The profitability study shows that a reduction of minimum load or retrofitting hydro reservoir storages with pump mode increase the hours of participation in balancing markets and machine utilisation, e.g. operating hours and frequency of machine starts. With the latter also wear of machines increases. Therefore, it is important to find the optimum in terms of machine starts and market benefits. Several benefits are presented per installed capacity to provide scalability and transferability of outcomes for other applications. Furthermore, the analyses make an important contribution to the European Projects of Common Interest discussion. Abstract : Highlights: Planned hydro projects in AT till 2030 avoid environmental damage costs of 1300 MEuro/a in CE. 3.5 GW turbine capacity in addition replaces 1 GW of thermal power capacity. Reducing minimum load of PHS by 50.